Biologically inspired cognitive architectures (BICA) for young scientists : proceedings of the First International Early Research Career Enhancement School (FIERCES 2016) /: proceedings of the First International Early Research Career Enhancement School (FIERCES 2016). ([2016]) - Unknown
No abstract available